Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.3390/ani8060097
|View full text |Cite
|
Sign up to set email alerts
|

Using GPS Technology to Understand Spatial and Temporal Activity of Kangaroos in a Peri-Urban Environment

Abstract: Simple SummaryKangaroo–human conflict is increasing in the peri-urban communities of the New South Wales (NSW) north coast in Australia. A way to assist in managing this conflict is to improve our understanding on the ecology of kangaroos in the peri-urban environment. We utilized modern Global Positioning System (GPS) technology to track adult male kangaroo movements in a peri-urban housing estate at Coffs Harbour, Australia, using both collars and temporary glue-on devices. We also assessed the effectiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Diel activity showed surviving kangaroos to be bimodal, moving greater distances between fixes in the morning periods than the afternoon or evening. This timing is similar to those found for eastern grey kangaroos by Henderson et al [ 14 ]. Seasonal shifts in these patterns were evident with activity occurring earlier in summer than for other seasons and extending further into daylight hours during winter.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Diel activity showed surviving kangaroos to be bimodal, moving greater distances between fixes in the morning periods than the afternoon or evening. This timing is similar to those found for eastern grey kangaroos by Henderson et al [ 14 ]. Seasonal shifts in these patterns were evident with activity occurring earlier in summer than for other seasons and extending further into daylight hours during winter.…”
Section: Discussionsupporting
confidence: 91%
“…Due to the low survival rate of collared kangaroos, the value of GPS telemetry for monitoring movement patterns, and hence assessing adaptation to a new environment, was not fully realised during this study. Other studies using this technology have reported on the benefits it provides, particularly for tracking long-distance movements [ 14 , 61 ]. If the primary aim is to determine survival rates only, VHF collars are likely to be a more cost-effective option.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Henderson et al. ), similar to that for kangaroos in most non‐urban settings (Jaremovic and Croft , , Moore et al. ).…”
Section: Discussionsupporting
confidence: 54%
“…Indeed, a meta-analysis of physiological responses of birds and mammals to habitat disturbance revealed consistent changes in stress hormones in response to habitat degradation (Messina et al 2018). An urban eastern grey kangaroo's home range is estimated at between 20 and 100 ha (Brunton et al 2018b, Henderson et al 2018, similar to that for kangaroos in most non-urban settings (Jaremovic and Croft 1987, 1991, Moore et al 2002. While it was not possible to measure the amount of continuous habitat for all study sites, at southern urban sites the average continuous habitat was approximately 140 ha, much larger than the average 40 ha of the northern urban sites.…”
Section: Discussionmentioning
confidence: 69%